THE ROLE OF THE INFORMATION-EDUCATIONAL ENVIRONMENT AND INTERNATIONAL EXPERIENCE IN THE CONTINUOUS PROFESSIONAL DEVELOPMENT OF PEDAGOGICAL STAFF (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
This article examines the role of the information-educational environment in the continuous professional development of pedagogical staff. It explores the factors that influence the effective organization of digital learning environments and analyzes their impact on the development of teachers’ competencies. Advanced educational experiences from Finland, Singapore, South Korea, and the United States are reviewed to highlight best practices in modern teacher development. The findings contribute to the development of methodological recommendations for modernizing teacher training and improving the professional development system in Uzbekistan.